Using a Monoclonal Antibody to Identify Patients with Type I and Type II von Willebrand’s Disease - Hall, Jeffrey D; Willis, Dean W; Evatt, Bruce L; Jackson, Debra W (Thrombosis and Haemostasis, 1987)
Three monoclonal antibodies produced against vWF:Ag by conventional hybridoma technique did not inhibit factor VIII coagulant activity (F.VIII:C) but did inhibit VIII ristocetin cofactor activity. The antibodies were used in an indirect competitive ELISA for quantifying von Willebrand’s antigen (vWF: Ag) and compared with values obtained by the Laurell technique using commercial antibody by means of a ratio: ELISA/Laurell. For one monoclonal BD2-CC9, vWF:Ag values obtained in the two assays were in good agreement for normal and hemophilia A plasmas (normal, n = 19, ratio = 1.13 ± .17, hemophilia A, n = 10, ratio = 0.91 ± .15). However, type II vWD patients had a disproportionately low value of vWF: Ag with the ELISA. Use of the ratio normalized the difference among individual plasma values and allowed a significant separation of type II vWD plasma (n = 9, ratio = 0.46 ± .19) from normal plasma (p = .0001) and type I vWD plasma (n = 8, ratio = 1.52 ± .34) from type II vWD plasma (p = .0003) using BD2-CC9. Although the sample size was small, the greater degree of discrimination among the vWD plasmas tested with BD2-CC9 (compared with the other two antibodies [CA3-AE4, CC6-BG10]) suggests that this antibody may recognize conformational epitopes that reflect the degree of multimeric polymerization of the vWF molecule rather than simply recognize a decreased number of antigenic sites in a basic subunit. BD2-CC9 may be valuable in investigating the various types of vWD and/or the process of polymerization of this complex protein.
Keywords: Monoclonal antibody; Factor VIII; von Willebrand factor; ELISA; Factor VIII related antigen